Dental treatment in a patient with Cornelia de Lange Syndrome: case report - Gomes, Luana Ferreira (2021)
Cornelia de Lange syndrome (CLS) is a rare genetic disease with an estimated prevalence of 1 in every 30,000 live births. The main features are distinct craniofacial disorders, abnormalities in the upper and lower limbs and intellectual deficit, varying between patients, being the main clinical diagnosis. The aim of the paper is to report a case of a patient with a dental impairment SCL. A 31-year-old male patient with a genetic diagnosis performed at the age of 3 years presented macrodontia, agenesis of upper lateral incisors, impacted teeth, crowding, protrusion of anterior teeth, caries, mandibular micrognathia, anterior open bite, posterior crossbite, palate ogival, periodontal disease and fissured tongue, therefore, he was submitted to dental treatment, under general anesthesia, due to non-collaboration for outpatient treatment. They were performed as tip extractions, restorations with composite resin in units 11 and 21, scaling of sub and supra gingival calculi, as well as topical application of fluoride. The patient remained in the hospital for a day and made a good recovery. The importance of a multidisciplinary team in monitoring patients with SCL, including dentists, should be highlighted, contributing to an improvement in the quality of life of these clients. Patients must have periodic follow-up with the dentist, including in the case reported, will be monitored every 03 months, due to the fact that it is a rare pathology, difficult to manage clinically, for the control and prevention of important dental changes.